Saturn's Deep Atmospheric Flows Revealed by the Cassini Grand Finale Gravity Measurements. Issue 2 (30th January 2019) - Galanti, E.; Kaspi, Y.; Miguel, Y.; Guillot, T.; Durante, D.; Racioppa, P.; Iess, L.
Abstract: How deep do Saturn's zonal winds penetrate below the cloud level has been a decades‐long question, with important implications not only for the atmospheric dynamics but also for the interior density structure, composition, magnetic field, and core mass. The Cassini Grand Finale gravity experiment enables answering this question for the first time, with the premise that the planet's gravity harmonics are affected not only by the rigid body density structure but also by its flow field. Using a wide range of rigid body interior models and an adjoint based optimization for the flow field using thermal wind balance, we calculate the flow structure below the cloud level and its depth. We find that with a wind profile, largely consistent with the observed winds, when extended to a depth of around 8, 800 km, all the gravity harmonics measured by Cassini are explained. This solution is in agreement with considerations of angular momentum conservation and is consistent with magnetohydrodynamics constraints. Plain Language Summary: Observations show strong east‐west flows at the cloud level of Saturn. These winds are strongest at the equatorial regions, reaching up to 400 m/s, about 4 times stronger than tornado strength winds on Earth. Yet until now we had no knowledge on how deep these winds penetrate into the interior of the gas giant. The gravity experiment executed during the Grand Finale stage (May–August 2017) of the NASA Cassini mission helps answering this question. It is well established that any large‐scale motion of the fluid would have a signature in the density distribution and therefore in the planet gravity field. If we can estimate the internal structure and shape of the planet, we might be able to decipher the depth of the winds from its signal in the gravity measurements. Moreover, the rigid‐body and flow contribution to gravity field are entangled together, therefore it is necessary to use a wide range of rigid‐body models in order to define the wind‐induced gravity signal. In this work we propose a solution to the problem. We find that the gravity measurements can be explained with a flow pattern, similar to that observed at the cloud level, penetrating to depths of more than 8, 000 km into the planet interior. This has important implications not only for the atmospheric dynamics but also for the interior density structure, composition, magnetic field, and core mass. Key Points: Cassini gravity measurements point to deep differential flows within Saturn Using a wide range of rigid body internal structure models, the required wind‐induced gravity signal is defined With a conservatively modified cloud‐level wind and an optimized vertical profile, extended to a depth of 8, 800km, all gravity measurements are explained